THE TWO-PHASE ENVELOPE CONSTRUCTION OF LNG, LPG, AND HYDROCARBON MIXTURES - KUSDIANTARA (NIM : 20111045), RUDY
Phase diagram (phase envelope) is a relation between temperature and pressure that shows the condition of equilibrium between the different phases of chemical compound, mixture of compounds, and solutions. Construction of phase diagram is an important issue in chemical thermodynamics and hydrocarbon reservoir. This is very useful for process simulation, reactor design hydrocarbons, and petroleum engineering studies. Here in this thesis, phase diagrams of the hydrocarbon mixtures are constructed. Phase diagram is computed from the bubble line, dew line, and the critical point. Bubble line and dew line are composed of bubble point and dew line, respectively. Bubble line is the first point at which the gas is formed when a liquid is heated. While, dew line is the first point where the liquid is formed when a gas is cooled. Critical point is the point where all the properties of gas and liquid are the same for the temperature, pressure, amount of substance, and others. Bubble point and dew point are calculated by solving the third order polynomial Equation of State and fugacity equation. Here, Newton-Raphson is used to compute the critical points. Critical points consist of the critical temperature and critical pressure. In this thesis, Critical temperature is calculated directly. Meanwhile, the critical pressure is calculated by using the Newton-Raphson method. Here, as case studies phase diagrams of the composition of the Liquefied Natural Gas (LNG), Liquefied Petroleum Gas (LPG), and a mixture of hydrocarbons are simulated using Matlab.